Wholesomeness of irradiated food: c - A joint FAO/IAEA/WHO Expert Committee; World Health Organization; Food and Agriculture Organization (FAO); International Atomic Energy Agency (IAEA) (Geneva : World Health Organization, 1981)
Reports the findings of an expert committee commissioned to evaluate the extent to which processing by ionizing radiation may affect the nutritional content, chemical composition, and microbiological safety of food. In a set of unprecedented recommendations, the committee determined that the irradiation of any food commodity up to an overall average dose of 10 kGy presents no toxicological hazard and, moreover, that toxicological testing of foods so treated was no longer required. The report is recognized as a landmark in that it established a maximum absorbed dose for the wholesomeness of irradiated food.
Keywords: wholesomeness -- irradiated food